2023
DOI: 10.1186/s10020-023-00602-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ACK1-targeted therapy efficacy in lung adenocarcinoma using chloroquine or bafilomycin A1

Abstract: Background Activated Cdc42-associated kinase 1 (ACK1) is a promising druggable target for cancer, but its inhibitors only showed moderate effects in clinical trials. The study aimed to investigate the underlying mechanisms and improve the antitumor efficacy of ACK1 inhibitors. Methods RNA-seq was performed to determine the downstream pathways of ACK. Using Lasso Cox regression analysis, we built a risk signature with ACK1-related autophagy genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…However, the capacity of the ESTIMATE immune scores to predict immunotherapy response in cancer is controversial. 70 , 71 , 72 , 73 , 74 Gao et al. observed that the low-risk group classified by a novel pyroptosis-related signature had higher ESTIMATE immune scores and exhibited better responses to ICIs than the high-risk group in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity of the ESTIMATE immune scores to predict immunotherapy response in cancer is controversial. 70 , 71 , 72 , 73 , 74 Gao et al. observed that the low-risk group classified by a novel pyroptosis-related signature had higher ESTIMATE immune scores and exhibited better responses to ICIs than the high-risk group in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%